2006
DOI: 10.1128/iai.00328-06
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis rattiInduces Contact-Independent Apoptosis, F-Actin Rearrangement, and Barrier Function Disruption in IEC-6 Cells

Abstract: Blastocystis is an enteric protozoan purportedly associated with numerous clinical cases of diarrhea, flatulence, vomiting, and other gastrointestinal symptoms. Despite new knowledge of Blastocystis cell biology, genetic diversity, and epidemiology, its pathogenic potential remains controversial. Numerous clinical and epidemiological studies either implicate or exonerate the parasite as a cause of intestinal disease. Therefore, the aim of this study was to investigate the pathogenic potential of Blastocystis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 50 publications
1
71
1
2
Order By: Relevance
“…The exposure of intestinal epithelial cells to Blastocystis sp. subtype 4 led to limited apoptosis not associated with compromise in host cell barrier function (192), suggesting that the parasite may exert an antiapoptotic effect on host cells. We recently reported a systematic in vitro study to investigate the effect of Blastocystis ratti (subtype 4) on a rat intestinal epithelial cell line (IEC-6) (192).…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The exposure of intestinal epithelial cells to Blastocystis sp. subtype 4 led to limited apoptosis not associated with compromise in host cell barrier function (192), suggesting that the parasite may exert an antiapoptotic effect on host cells. We recently reported a systematic in vitro study to investigate the effect of Blastocystis ratti (subtype 4) on a rat intestinal epithelial cell line (IEC-6) (192).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…subtype 4 led to limited apoptosis not associated with compromise in host cell barrier function (192), suggesting that the parasite may exert an antiapoptotic effect on host cells. We recently reported a systematic in vitro study to investigate the effect of Blastocystis ratti (subtype 4) on a rat intestinal epithelial cell line (IEC-6) (192). The assays were carried out using Millicell cell inserts, which facilitated the study of contact-independent effects on host cells via parasite secretions.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors also showed that coincubation of intestinal epithelial cells of rat interstitial IEC6 with either Blastocystis sp. ST4 isolates or parasite lysates induced the apoptosis of host cells [Puthia et al 2006] in a contactindependent manner. A decrease in transepithelial resistance and an increase in epithelial permeability were also observed and could be explained by the rearrangement of actin filaments [Tan et al 2010;Mirza et al 2012].…”
Section: Pathophysiology Of Blastocystosismentioning
confidence: 99%
“…Endoscopic and permeability studies of the intestine in a cohort study of Blastocystis-infected immunocompetent individuals failed to find any significant intestinal inflammation or impairment of the intestinal permeability barrier (Zuckerman et al, 1994). Fresh Blastocystis isolates, though, have been demonstrated to cause significant cytopathology of Chinese hamster ovary cells (CHO), adenocarcinoma HT-29 cells and rat intestinal epithelia (IEC-6) cells in culture (Puthia et al, 2006;Walderich et al, 1998). Metronidazole, paromomycin and ketoconazole have been used as therapeutic agents with mixed success (Zierdt et al, 1983;Dunn & Boreham, 1991;Haresh et al, 1999;Nanba et al, 2003).…”
Section: Introductionmentioning
confidence: 99%